Removal of Atrazine by Biogenic Manganese Oxide in Batch and Fixed-Bed Column Reactors - Gulcek, Betul; Tepe, Ozlem (Taylor & Francis Inc, 2022)
Atrazine is a widely used herbicide today and is usually detected at high concentrations in aqueous media. Its presence in aquatic environments poses a serious risk to human and environmental health. Adsorption is a promising technology for the removal of persistent organic materials. In this study; dried biogenic manganese oxide (BMO) as a novel adsorbent material was used to control the atrazine pollution. The removal of atrazine by dried BMO was investigated in batch and fixed-bed column reactors. Batch studies revealed that maximum atrazine removal was 98.1% at a temperature of 50 degrees C, pH: 12.0 and an atrazine concentration of 0.5 mg L-1. The maximum atrazine adsorption capacity was 2.124 mg g(-1) at 50 degrees C, pH: 12.0 and atrazine concentration of 10 mg L-1. The Freundlich isotherm fitted very well to experimental data. Adsorption followed the pseudo-first-order type kinetic. Thermodynamic values such as Gibbs free energy, enthalpy and change in entropy were measured as -26.02 kJ mol(-1) (30 degrees C), 106.48 kJ mol(-1) and 0.43947 kJ mol(-1) K-1, respectively and the adsorption process was found to be spontaneous and endothermic. The effects of parameters such as feed flow rate, initial atrazine concentration and BMO amount on the atrazine removal were investigated in a fixed-bed column reactor. When a flow rate of 4 mL min(-1), atrazine concentration of 2 mg L-1 and BMO of 2 g were used, the equilibrium atrazine uptake (q(eq)) was 0.41 mg g(-1).
Keywords: Adsorption; atrazine; dried biogenic manganese oxide (BMO); fixed-bed column reactor; pesticide removal